Preliminary processing of spectra for analysis by method of differential optical absorption spectroscopy - Bruchkouski, Ilya I.; Svetashev, Alexander G.; Demin, Victar S.; Barodka, Siarhei K.; Anikin, Petr P.; Krasouski, Alexander N. (Journal of the Belarusian State University. Physics, 2019)
That work is dedicated to investigation of the possibilities for the DOAS (Differential Optical Absorption Spectroscopy) method accuracy improvement by the comparative calibration procedure using a reference instrument that has been applied to the Multi Axis Recorder of Spectra (MARS-B) instrument. The instrument has been developed at the Belarusian State University. A comparative analysis of the measurements obtained by MARS-B during the international inter-comparison campaign CINDI-2 (Second Cabauw Intercomparison of Nitrogen Dioxide Measuring Instruments, Cabauw, Netherlands, 2016) has been carried out. As a result of MARS-B measurements, the differential slant column densities of trace gases have been obtained for nitrogen dioxide, ozone, water, HONO, HCHO, and oxygen dimer. To investigate the possibilities for the DOAS method accuracy improvement, analysis of the sky radiance spectra series over the wavelength range 335–373 nm has been carried out. The analyzed spectra have been recorded simultaneously by the MARS-B instrument and by the instruments of other CINDI-2 participants. A method to reduce the error of the differential slant column densities retrieval by applying a digital low-pass filter in the preliminary processing of the spectra has been presented.